Zanclea hicksoni ... - Soto, Joan J.; Peña, Álvaro L. (Zenodo, 2019)
Zanclea hicksoni (Stepanjants, 1972) (Fig. 4 j–o) Material examined. ANT XV/3: 48-31, a single polyp, c. 3 mm high, on O. terranovae; ANT XVII/3: 111-9, numerous polyps, up to 5 mm high, on T. longstaffi and E. generale. Remarks. According to Peña Cantero et al. (2013), Z. hicksoni is conspecific with Corynidae Species B Hickson & Gravely, 1907. The species was later described as Gemmaria hicksoni Stepanjants, 1972. As previously noted by Hickson & Gravely (1907), polyps examined here are provided with hydrorhizal filaments which anchor them to the substrate (Fig. 4l). Additionally, we have observed some large specimens with linear clusters of 3–5 tentacles, being the central one larger (Fig. 4n). These two characteristics are diagnostic features of the genus Monocoryne Broch, 1910 (Fam. Candelabridae Stechow, 1921) according to Stepanjants et al. (2003). Conversely, there are no Zanclea species with those characters (cf. Bouillon et al. 2006). According to Stepanjants et al. (2003), the tentacles of ... : Published as part of Soto, Joan J. & Peña, Álvaro L., 2019, Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica), pp. 1-78 in Zootaxa 4570 (1) on page 20, DOI: 10.11646/zootaxa.4570.1.1, http://zenodo.org/record/2608527 ...